A Case of De Novo Antiglomerular Basement Membrane Disease Presenting during Pregnancy. (18th March 2021) - Lodhi, F. A. K.; Akcan, T.; Mojarrab, J. N.; Sajjad, S.; Blonsky, R.
Abstract : Background . Acute kidney injury (AKI) requiring dialysis during pregnancy is uncommon. We present a case of a young female diagnosed with antiglomerular basement membrane (anti-GBM) disease during pregnancy. Case Presentation . A 23-year-old woman approximately 15 weeks pregnant experienced weakness, nausea, vomiting, and anorexia for one week and anuria for 48 hours. No known drug allergies and no significant social or family history for kidney or genitourinary disease were reported. Laboratory analysis revealed anemia, life-threatening hyperkalemia, AKI, and elevated antiglomerular basement membrane (GBM) antibodies. Renal biopsy revealed 100% cellular crescents, confirming the diagnosis. The patient was treated using plasmapheresis and methylprednisolone followed by oral steroids, azathioprine, and tacrolimus. At 24 weeks and 4 days of gestation, the patient had hypoxic respiratory failure as well as preterm premature rupture of membranes. Due to the development of infection and lack of renal recovery, immunosuppression was discontinued. At 28 weeks and 0 days of gestation, the patient developed uncontrollable hypertension requiring emergent delivery. Postpartum, her hypertension improved without signs of preeclampsia though still requires dialysis. Discussion . Pregnancy presents a unique challenge for providers treating patients with anti-GBM disease. Fetal safety should be considered and risks thoroughly discussed with the patient when choosing an immunosuppressive regimen for this condition.